Fluorescence electrochemical microscopy: capping agent effects with ethidium bromide/DNA capped silver nanoparticles - Tanner, E; Sokolov, S; Young, N; Batchelor-McAuley, C; Compton, R (Wiley, 2017)
Fluorescence microscopy and electrochemistry were employed to examine capping agent dynamics in silver nanoparticles capped with DNA intercalated with ethidium bromide, a fluorescent molecule. The capped NPs were studied first electrochemically, demonstrating that the intercalation of the capping agent promotes oxidation of the silver core, occurring at 0.50 V (vs Ag, compared with 1.15 V for Ag NPs capped in DNA alone). Second, fluorescence electrochemical microscopy revealed that the electron transfer from the nanoparticles is gated by the capping agent, allowing dynamic insights unobservable using electrochemistry alone.